Modelling and simulation of nonlinear phenomena in microstructured optical fibres - Rodrigues, Sílvia Maria Gouveia (2020)
This Ph.D. embraced the study of the nonlinear optical phenomena occurring in microstructured optical _bres (MOFs), also called photonic crystal fibres (PCFs). In these fibres, there are the solid-core MOFs (SC-MOFs) and the hollow-core MOFs (HC-MOFs), which allow guided propagation of light in a diversity of conditions that are not possible with conventional fibres. The mechanisms of guidance of these fibres were studied, which for SC-MOFs and HC-MOFs included the computation of the guided modes, and for the latter included also the calculation of photonic bands, bandgaps, and density of states. In addition, the dispersion curves and the nonlinearity coefficients of SC-MOFs and of gas-filled HC-MOFs were calculated. The nonlinear propagation of ultra-short pulses of light in those fibres was modeled and simulated. With the simulations of this work, the supercontinuum generation, and the UV-light generation were predicted in certain conditions. In the last part of this work the electromagnetically induced transparency effect in hollow core fibres was investigated in detail.